Investigating the Pygmalion Effect in Managers on the Sales Performance of Employees in Holiday Chain Store branches - Mansour Tahbaz; Abbasali Rastgar; Davood Feiz (‫مدیریت بازرگانی, 2023)
Objective One of the most important factors for employees' success is focusing on the positive outcome of each situation, according to which they increase their trust and commitment. Hence, those who are positively focused can act very boldly and continue their efforts until achieving the desired result. The Pygmalion effect is a psychological principle related to the effective management of people. If employees think that their organization will be successful, they may subconsciously take action on this issue. As a sales manager, your ability to develop and retain sales representatives is critical to your company's performance and future success. Retaining employees in sales is still an important issue. Also, when salespeople are gaining skills to prepare for and succeed in their role, they are more likely to be job-satisfied and feel that their employer values their work. These factors reduce the likelihood of their willingness to resign. Holliday Chain Store as an enterprise is no exception to this rule. For this purpose, this study investigates the Pygmalion effect in branch managers on improving the sales performance of employees in the named chain store.